PELAKSANAN SANKSI PIDANA ADAT MINANGKABAU DI NAGARI KOTO TINGGI KECAMATAN BASO KABUPATEN AGAM - Febby Febby; Erry Gusman; Syaiful Munandar (Ensiklopedia of Journal, 2023)
Minangkabau customary law also recognizes the existence of customary criminal law. Customary criminal law (material) in Minangkabau is called the nan salapan law while the customary (formal) procedural law is called the nan duo puluah law. Nagari Koto Tinggi, Agam Regency, which is a part of the Unitary State of the Republic of Indonesia, besides being subject to If there is a criminal case, the Minangkabau customary criminal provisions are still in force. The purpose of this research is to find out the forms of offenses that have been imposed, the process of resolving the imposition of sanctions on perpetrators and obstacles and solutions made to overcome obstacles in imposing customary criminal sanctions. in Kenagarian Koto Tinggi District of Baso in the implementation of Minangkabau customary sanctions. The results of the research found that in Nagari Koto Tinggi the forms of customary offenses that had occurred were in the form of dago dagi, false discord, theft and same-ethnic marriage. Customary offense cases are resolved by the Adat Peace Council which has 9 judges who have no relation to the perpetrators. The only obstacle in imposing sanctions is in cases of wrongdoing. Criminal sanctions such as those that occurred in Nagari Koto Tinggi need to be maintained if it is necessary to expand the provision of these sanctions to nephews' children who commit other crimes such as corruption, because corruption is a crime of "stealing" according to customary law.